ADSORPSI METHYLENE BLUE MENGGUNAKAN ADSORBEN ASAM FULVAT (AF) DARI TANAH GAMBUT SAMBOJA KALIMANTAN TIMUR - Fransiska Febriani; Soerja Koesnarpadi; Ika Yekti Liana Sari (PROSIDING SEMINAR KIMIA, 2022)
Research on the adsorption of methylene blue with fulvic acid (AF) adsorbent from peat soil has been carried out. The initial stage is the extraction of AF from the peat soil of the Samboja area of East Kalimantan. Extraction was carried out with a solution of 1 M NaOH and 12 M HCl(p). The results obtained a yellow-brown solid fulvic acid. The optimization of methylene blue adsorption by AF was obtained, namely a contact time of 120 minutes at pH 3 and an optimum concentration of 40 mg/L and an adsorption capacity of 0.98 mg/g. Keywords: Adsorption, fulvic acid, methylene blue